Odpowiedzi

2010-02-08T22:13:22+01:00
1.a(a+b+c)-b(a-b+c)-c(a-b-c)=a kwadrat+ab+ac-ba+b kwadrat-bc-ca+cb+c kwadrat
2.x(x²+2x+1)-(-4x³+8x²-6):2=x sześcian+2x sześcian+x+(4x sześcian-8x kwadrat+6):2=7x sześcian+x+8x kwadrat+6 :2
3.12b×(b-1:4)+14×(b²-2b:21)-(b-b²:3)=12b kwadrat+12b:4+14b kwadrat-28b :21-b+b:3
4 1 4
Najlepsza Odpowiedź!
2010-02-08T22:17:23+01:00
1. a(a+b+c)-b(a-b+c)-c(a-b-c) /////wymnażamy nawiasy
a²+ab+ac-ab+b²-bc-ac+bc+c²= //////redukujemy
=a²+b²+c²

2. x(x²+2x+1)-(-4x³+8x²-6):2= //////////wymnażamy nawiasy
=x³+2x²+x+2x³-4x²+3= ///////redukujemy
=3x³-2x²+x+3

3. 12b×(b-1:4)+14×(b²-2b:21)-(b-b²:3)= ///skracamy liczbę przed nawiasem z dzieleniem w nawiasie
=3b(b-1)+⅔(b²-2b)-⅓(b-b²)= ////wymnażamy nawiasy
=3b²-3b+⅔b²-4/3 b - ⅓b + ⅓b²= ////redukujemy
4b²-4⅔b
4 5 4